Penurunan Intensitas Pendidikan Islam terhadap Fluktuasi Emosional pada Remaja Usia Pertengahan - Muktar, Muktar (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
Emotional distress during middle adolescence is a psychological phenomenon that is often experienced by adolescents due to significant physical, hormonal, and social changes. This study aims to understand the factors that cause emotional distress in adolescents aged 14 to 16 years and their impact on their social, cognitive, and psychological development. Through a qualitative approach, data were collected using semi-structured interviews, observations, and questionnaires to identify the level of emotional distress and the factors that influence it. The results showed that emotional dependence during this period was influenced by internal factors, such as hormonal changes and identity search, as well as external factors, including social pressure, family dynamics, and peer roles. This emotional weakness can interfere with adolescents' social relationships, academic achievement, and mental health, as well as worsen their decision-making and emotional regulation. Based on these findings, interventions involving counselling, social and emotional education (SEL), as well as support from families and schools are recommended to help adolescents better manage their emotions and improve their psychological well-being. This research provides insight into the importance of a holistic approach in supporting adolescents to face emotional challenges during this transition period.